„Mut des Wortes“ – „Mut der Tat“? ‚Weibliche‘ Bühnen des Wissens in einem deutschen Prag der ersten Republik - Benedik, Stefan (Österreichische Zeitschrift für Geschichtswissenschaften, 2010)
The cultural landscape of the capital of the first Czechoslovak Republic was marked by many different spaces of communication which were closely linked to certain communities (formed on the basis of national / ‘ethnic’ association). The article focuses on the example of two institutions and their lectures as such spaces that were specialised on producing, negotiating, presenting, applying and positioning knowledge. Theory and practice – words and action – do not appear there as opposites, but rather as inseparable threads of the same fabric. In past and present narration, those are covered by a reducing, yet powerful classification as being ‘female’ – a description which is based on symbolical aspects only (and not, e.g. on a gendered division of labour). Examining contexts and implications of this ascription, the article reveals reasons for the invisibility of paradoxes and diversity within the perceptions of these spaces of knowledge.